Effects of Nonpharmacological Interventions on the Components of Metabolic Syndrome in Tirunelveli City Police (International Journal of Physiology, 2020)
Background: Life style modifications like walking, slow deep breathing and dietary modifications play amajor role in modifying the components of metabolic syndrome. This study was conducted to determinethe effects of non-pharmacological interventions on components of metabolic syndrome among the policepersonnel in Tirunelveli city.Method: This is a before and after intervention study in which 44 police personnel working in Tirunelvelicity in the age group of 30-58 years with metabolic syndrome were included. After getting due permissionfrom the Deputy Commissioner of Police, Tirunelveli and Head of Department of Bio chemistry Department,Institutional Ethical Committee clearance and oral informed consent from the volunteers the study wasstarted. The study was conducted during the period from August to November, 2013. Height, weight, waistcircumference, blood pressure estimation and bio-chemical investigations were measured at baseline and 12weeks after intervention in the study group.Results: It is found that the physiological parameters measured before and after non pharmacologicalintervention in the study group indicate a distinct and statistically significant reduction in all the values anda significant increase in HDL.Recommendation: Physical fitness schedule, along with stress alleviation techniques and dietarymodifications may be made mandatory to keep the police personnel physically and mentally healthy.